Antioxidant Capacity and Total Phenolic Content of Cocoa (Theobroma Cacao L.) Beans from Different Countries - Othman, Azizah (2005)
This study was conducted to investigate the antioxidant capacity, phenolic and (-) epicatechin contents of cocoa beans from different, countries, namely Malaysia, Ghana, Cote d'Ivoire and Sulawesi. A simple linear regression test was used to analyse the relationship between total phenolic and antioxidant capacity. Antioxidant capacity was assayed using four different assays namely, bleaching, DPPH (2,2-diphenyl-$-picrylhydrazyl), ferric reducinghtioxidant potential (FRAP) and trolox equivalent antioxidant capacity WAC) methods. To estimate the content of total phenolic, an assay using Folin-Ciocalteu reagent was used. High-performance liquid chromatography (HPLC) was used to determine the (-) epicatechin content. In this study, two extraction media were used namely, ethanol and water. Between the twc extracts, ethanolic extract of cocoa beans showed higher antioxidant capacity compared to water extract except for $-carotene bleaching assay. The antioxidant activity of LJ ethanolic extracts based on fkarotene bleaching method followed the order of Cote d71voire > Malaysia > Ghana > Sulawesi. Water extract of Cote d"1voirian beans showed the highest antioxidant activity, followed by Ghana, Malaysia and Sulawesi with a significant difference at p < 0.05. All ethanolic extracts showed higher scavenging activity than that of water extract based on DPPH method. Ghanaian beans exhibited the highest scavenging activity, followed by Cote d'hoirian, Malaysian and Sulawesian. The scavenging activity of water extracts was in the order of Ghana > Malaysia > Cote d'Ivoire > Sulawesi. For FRAP method, Sulawesian beans had the highest antioxidant potential, followed by Malaysia, Ghana and Cote d'Ivoire. There was no significant difference between Sulawesian and Malaysian beans. The antioxidant potential of water extracts was in the order of Sulawesi > Ghana > Malaysia > Cote d'Ivoire. In TEAC assay, Sulawesian beans exhibited the highest antioxidant value for both ethanolic and water extracts, followed by Malaysia, Ghana and Cote d'Ivoire with a significant difference at p < 0.05. Malaysian beans showed significant highest value (p < 0.05) in phenolic content for both ethanolic and water extracts, followed by Sulawesian, Ghanaian and Cote d'hoirian. For epicatechin content, Sulawesian beans exhibited significant highest (p < 0.05) amount followed by Malaysian, Ghanaian and Cote d'lvoirian. The results indicated that different assays revealed different antioxidant values. Moreover, the cocoa beans extracts from four different countries of origin showed different antioxidant capacities. A positive and high correlation were found between total phenolic and antioxidant potential (FRAP) for both ethanolic (R = 0.764) and water extracts (R = 0.782). While a positive moderate and low correlation were found between total phenolic content and TEAC for water and ethanolic extracts (R = 0.685, R = 0.286), respectively. 11 However, total phenolic content has negative correlation with antioxidant and scavenging activity. Antioxidant capacity of cocoa beans could be contributed by phenolic substances, through reducing potential. Moreover, (-) epicatechin content showed a positive and high correlation with antioxidant potential (ethanolic extracts, R = 0.837; water extracts, R = 0.789) and TEAC value (ethanolic extracts, R = 0.918; water extracts, R = 0.895) for both ethanolic and water extracts. Thus, indicating that, (-) epicatechin could be one of the phenolic contributes towards antioxidant capacity. Results indicated that antioxidant capacity, total phenolic and (-) epicatechin content of Malaysian beans were comparable to Ghanaian and Cote d'Ivoirian beans.